SWOT analysis of land area-based and value-based property rating - Baba, Habu Mallam; Kasim, Rozilah; Usman Alhaji, Muktar; Ali Abdu, Abdullahi; Auwal, Umar; Adam Muhammad, AbdulAzeez (Science Arena Publications, 2018)
The property rating can be on Value-based rating Assessment (VbRA) or Area-based Rating Assessment (AbRA). This study examined the suitable assessment of Bauchi metropolis, Nigeria. The materials used were published books and journal articles, and SWOT technique was applied to analyse the identified variables, then the strengths, weaknesses, opportunities and threats were sorted out. The facts from the SWOT matrix were assimilated into existing local scenario to strategically decide the appropriate assessment procedure for raising the local revenue for financing the provision and maintenance of municipal infrastructure and facilities. The study found Area-based Rating Assessment (AbRA) as the most appropriate rating assessment procedure for the study area.